"An Examination on Supply Chains to Meet the Increasing Demands for Electric Vehicles (EVs)" - Aphisawetkarn, Woraphat (2012)
Abstract The combustion of fossil fuels has been a central concept of energy production over the past few decades, providing a significant source of energy to the daily life. Excessive production has resulted in fossil fuels becoming scarce and raising environmental concerns of greenhouse gas emissions. Nowadays, alternative technologies are developing in order to elude the problems associated with the fossil fuels. Among many energy consumption technologies, the automotive is a significant transportation segment governing most of the economic sectors in the world. However, with concerns of utilising fossil fuels, the automotive industry has developed an alternative energy consumption vehicle as well as other industries. The electric vehicle (EV) is a proposed solution to eventually replace the current fossil fuel consumption vehicle. Instead of using solely petroleum, the EV uses electricity as fuel which can be widely sourced. For long periods of driving, the electrical energy is stored in a rechargeable battery which is the main indicator of the EV's performance. Advancements in battery technology will impact on the supply chain of EVs, as a change in demand for particular technologies will affect the uncertainties of the particular supply chain. In this literature-based view, a closed-loop supply chain (CLSC) is considered for EVs, which will mainly focus on the rechargeable battery. The report will discuss topics of interest and state the objectives to be explored. A brief overview of an automotive industry, especially on various economic aspects, and information on supply chain management is presented. Furthermore, a concise study of EVs, including a suitable business model, is carried out. Finally, an analysis of the CLSC involved in the electric vehicle sector is proposed to evaluate its impact on the automotive industry.